The Implications of Using Fusha and 'Amiyah Arabic on Indonesian Students at Al Azhar University in Egypt: A Sociolinguistic Perspective - Agustin, Triani; Muttakin, Khaerul; Azmi, Faqih Tsabitul; Wahid, Ilham Dhya'ul (Mantiqu Tayr: Journal of Arabic Language, 2026)
The use of Fuṣḥa and 'Āmiyah in the context of Islamic higher education in Egypt creates complex linguistic dynamics for Indonesian students at Al-Azhar University. This study aims to analyze the relationship among the choice of Arabic language varieties, academic demands, and students' social adaptation in a real diglossic environment. Using a descriptive qualitative approach, data were collected through open-ended questionnaires and semi-structured interviews with 25 Indonesian students and subsequently analyzed using content analysis from a sociolinguistic perspective. The results show that Fuṣḥa functions not only as a formal academic medium but also as a symbol of scholarly authority and legitimacy of academic identity. At the same time,‘Āmiyah becomes the main instrument in building social relations, understanding local culture, and achieving practical communication effectiveness. The continuous interaction between the two varieties fosters adaptive communicative competence, characterized by strategic code-switching, sensitivity to social norms, and pragmatic flexibility. These findings show that Arabic diglossia functions as a productive linguistic resource rather than merely a barrier to learning. This study provides a conceptual contribution to the study of Arabic sociolinguistics. It offers pedagogical implications for the development of Arabic language learning for foreign speakers that align with sociolinguistic realities.